Experimental investigation of novel solid oxide electrolyser cell for direct conversion of flue gas to syngas - Syed Alwi Alsagoff (Nanyang Technological University, 2021)
Wide-spread consumption of fossil fuels has led to serious environmental problems. Flue gas (main components being CO2 and H2O) discharged from thermal power plants amount for a major part of CO2 emissions globally. All the nations and governments are planning and taking measures to achieve carbon reduction and even carbon neutralisation as the ultimate goal. Two effective ways for this purpose include carbon capture, utilization, and storage (CCUS) and use of renewable energy to replace the conventional fossil fuel energy. Direct flue gas co-electrolysis using high temperature solid oxide electrolysis cell (SOEC) and renewable electricity is an ideal choice for carbon utilisation and energy storage. The syngas produced by flue gas co-electrolysis can be converted to electricity using SOEC or can be used to produce synthetic liquid fuels using Fischer-Tropsch process. In contrast to a traditional power plant, where air is used instead of oxygen and produces significantly high amounts of nitrogen with 5% CO2, direct co-electrolysis of flue gas for syngas production using SOECs is useful for an oxy-combustion power plant, where oxygen is used instead of air. Hence, the product gases would be nothing more than CO2, H2O, and excess oxygen. This project aims to develop an efficient high temperature SOEC for conversion of flue gas to syngas. The electrochemical behaviours of two sets of symmetrical cells with LSCM-GDC electrodes and LSCMN-GDC electrodes have been studied under various electrolysis conditions, involving operating temperature, inlet gas composition and concentration, and novel SOEC operation mode with methane in the air electrode chamber. Very interesting results have been obtained from the project experiments conducted. By introducing nickel element into the LSCM oxide, we have observed a consistently better performance from the symmetrical SOEC, giving low resistances overall as well as the current density. The ohmic resistance of the cell with LSCMN-GDC electrodes is reduced by 50% in comparison with that for the cell with LSCM-GDC electrodes. The current-voltage responses have demonstrated much higher current densities from the cell with LSCMN-GDC electrode, indicating a substantial cell performance improvement as a result of Ni doping into the LSCM material. The effects of having methane in the air electrode chamber, also referred as the novel solid oxide operation mode are positive. Higher current densities have been measured under novel SOEC operation mode from both symmetrical cells with LSCM-GDC electrodes and cells with LSCMN-GDC electrodes, indication of the advantage of the novel SOEC operation mode over the conventional SOEC mode. In addition, syngas can also be produced at the fuel electrode through flue gas electrolysis.